Alternative Wnt-signaling axis leads to a break of oncogene-induced senescence - Kluge, Viola; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Zimmermann, Tom; Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cell Death & Disease, 2024)
Oncogene-induced senescence (OIS) is an important process that suppresses tumor development, but the molecular mechanisms of OIS are still under investigation. It is known that BRAFV600E-mutated melanocytes can overcome OIS and develop melanoma, but the underlying mechanism is largely unknown. Using an established OIS model of primary melanocytes transduced with BRAFV600E, YAP activity was shown to be induced in OIS as well as in melanoma cells compared to that in normal epidermal melanocytes. This led to the assumption that YAP activation itself is not a factor involved in the disruption of OIS. However, its role and interaction partners potentially change. As Wnt molecules are known to be important in melanoma progression, these molecules were the focus of subsequent studies. Interestingly, activation of Wnt signaling using AMBMP resulted in a disruption of OIS in BRAFV600E-transduced melanocytes. Furthermore, depletion of Wnt6, Wnt10b or β-catenin expression in melanoma cells resulted in the induction of senescence. Given that melanoma cells do not exhibit canonical Wnt/β-catenin activity, alternative β-catenin signaling pathways may disrupt OIS. Here, we discovered that β-catenin is an interaction partner of YAP on DNA in melanoma cells. Furthermore, the β-catenin–YAP interaction changed the gene expression pattern from senescence-stabilizing genes to tumor-supportive genes. This switch is caused by transcriptional coactivation via the LEF1/TEAD interaction. The target genes with binding sites for LEF1 and TEAD are involved in rRNA processing and are associated with poor prognosis in melanoma patients. This study revealed that an alternative YAP-Wnt signaling axis is an essential molecular mechanism leading to OIS disruption in melanocytes. (Figure presented.).
CRIS-Team Scopus Importer:2024-03-01

Detection and quantification of cellular senescence in human melanocytes and melanoma cell lines - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (Cells, 2022)
Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal experience. This study aims to provide a comprehensive comparison of biomarkers and cellular characteristics used to detect senescence in melanocytic systems. Each marker was assessed in primary human melanocytes that overexpress mutant BRAFV600E, as it is commonly found in melanocytic nevi, and melanoma cells after treatment with the chemotherapeutic agent etoposide. The combined use of these two experimental settings is thought to allow profound conclusions on the choice of senescence biomarkers when working with melanocytic systems. Further, this study supports the development of standardized senescence detection and quantification by providing a comparative analysis that might also be helpful for other cell types and experimental conditions.
CRIS-Team Scopus Importer:2022-05-13
Keywords: beta-galactosidase; melanocyte; melanoma; senescence

Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence

Molecular mechanisms of OIS breakdown in the context of melanoma formation - Kluge, Viola; Zimmermann, Tom; Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

The Nuclear Envelope Proteins LMNB1 and LBR influence the Chromatin Structure and Senescence Processes in Melanoma - Lämmerhirt, Lisa; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Kuphal, Silke; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23